Kontribusi Keterlibatan Ayah dan Keberysukuran dalam Memprediksi Kesejahteraan Psikologis pada Remaja - Illene Nathania Evelyna Zeva; Isrida Yul Arifiana; Suroso Suroso (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2026)
Psychological well-being plays an essential role in supporting adolescent development, particularly in early adolescence, which is characterized by significant changes in biological, cognitive, and socio-emotional aspects. The family environment, particularly the father's involvement, along with positive characteristics such as gratitude is believed to contribute to improving adolescent psychological well-being. This study aims to analyze the correlation between father involvement and gratitude with psychological well-being in junior high school students. The research method used is a quantitative approach with a correlational design. The study sample consisted of 184 junior high school students obtained through an accidental sampling technique. The research instruments included a father involvement scale, a gratitude scale, and a psychological well-being scale. Data analysis was conducted using multiple linear regression tests. The results showed a significant correlation between father involvement and gratitude with adolescent psychological well-being. Both independent variables act as positive and significant predictors of adolescent psychological well-being, with gratitude showing a more dominant contribution.